Service-learning and educating in challenging contexts: international perspectives - Murphy, Timothy, Dr; Tan, Jon (Continuum, 2012)
"Explores best practice for engagement with challenging educational contexts through service-learning drawing on the contributors' international experience"--
Includes bibliographical references and index